The Possible Contribution of P-Glycoprotein in the Protective Effect of Paeonol against Methotrexate-Induced Testicular Injury in Rats - Mohamed A. Morsy; Asmaa M. Abdel-Aziz; Sara M. N. Abdel-Hafez; Katharigatta N. Venugopala; Anroop B. Nair; Seham A. Abdel-Gaber (MDPI AG, 2020)
Paeonol, a phenolic ingredient in the genus Paeonia, possesses antioxidant and anti-inflammatory effects. Methotrexate (MTX) is a commonly used chemotherapeutic agent; however, its germ cell damage is a critical problem. P-glycoprotein (P-gp), an efflux transporter, is a member of the blood-testis barrier. The present study evaluated the protective effect of paeonol on MTX-induced testicular injury in rats with the exploration of its mechanism and the possible contribution of P-gp in such protection. Testicular weight, serum testosterone, and testicular P-gp levels were measured. Testicular oxidant/antioxidant status was evaluated via determining the levels of malondialdehyde, total nitrite, reduced glutathione, and superoxide dismutase activity. The inflammatory cytokine tumor necrosis factor-alpha (TNF-α) and the apoptotic marker caspase 3 were estimated immunohistochemically. Testicular histopathology and spermatogenesis scores were also examined. MTX caused histopathologically evident testicular damage with decreased testicular weight, testosterone level, and spermatogenesis score, as well as significant increases in oxidative, inflammatory, and apoptotic responses. Paeonol significantly restored testicular weight, testosterone level, spermatogenesis score, and oxidant/antioxidant balance. Moreover, paeonol increased the testicular P-gp level and significantly decreased TNF-α and caspase 3 immunostaining. In conclusion, paeonol offered a protective effect against MTX-induced testicular injury through its antioxidant, anti-inflammatory, and antiapoptotic effects, as well as by increasing testicular P-gp level.